Pengaruh Capital Adequacy Ratio, BOPO, dan Loan to Deposit Ratio terhadap Non-Performing Loan pada Bank Konvensional di Indonesia yang Terdaftar BEI - Ade Sumarni; Dien Noviany Rahmatika; Eva Anggra Yunita (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study aims to examine the effect of the Operating Expenses to Operating Income ratio (BOPO), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and the implementation of Good Corporate Governance (GCG) on non-performing loans (NPL) in conventional banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative approach using secondary data from annual financial statements. The sample was selected using purposive sampling, resulting in 33 banks observed over five years (165 observations). Multiple linear regression analysis was applied using IBM SPSS software. The findings indicate that BOPO and LDR have a positive and significant effect on NPL. Meanwhile, CAR has a negative but insignificant effect on NPL. In contrast, GCG has a negative and significant effect on NPL. This study is expected to provide insights for banking management to improve operational efficiency, strengthen credit risk management, and enhance corporate governance practices in order to reduce bad credit risk.